KEPATUHAN PENGGUNAAN KANTONG PLASTIK OLEH PELAKU USAHA DI PASAR KRANJI BARU KOTA BEKASI - Alifya Salsabila; Hardi Warsono; Retno Sunu Astuti (Journal of Public Policy and Management Review, 2023)
Plastic waste is a very well-known problem because it has a long decomposition time limit, which is 100-500 years and can release a toxic substance (methane) when exposed to sunlight and if not decomposed immediately it can clog waterways and cause flooding. The step taken by the Bekasi City government is to create Bekasi Mayor Regulation No. 61 of 2018 which regulates the use of plastic bags, was made with the aim that people get used to using personal shopping bags. This study aims to describe and analyze the results of the implementation of Bekasi Mayor Regulation No. 61 of 2018 which has been running for 3 years at Pasar Kranji Baru Bekasi, as well as finding out the factors in the business actors. The research method used in this research is descriptive through a qualitative approach and uses primary data through questionnaires, as well as secondary data through journals, books, literature, etc. The research was then analyzed using Microsoft Excel and showed a low adherence rate of 44.8%. As for the inhibiting factors, namely the knowledge that business actors are still low, the habit of business actors using conventional plastic bags, and there are no sanctions for violators.